Kontekstualisasi Kemukjizatan Sastrawi al-Qur’ân - Husein Aziz (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2017)
This article examines the wording, tone, and meaning of the Qur’ân, and its effective and persuasive language in presenting ideas, thoughts, and the psychological situation. The study uses modern linguistic approach, combined with synchronic and diachronic methods. This article reveals the following conclusions: first, the description of the Qur’ân is formed from a series of words chosen carefully in accordance with the tone of meaning, and is organized in accordance with the ideas and situations presented; second, the properties of the Qur’ân in describing the ideas, thoughts and situation is very connotative, leading to multiple interpretations, and demonstrating the effect of musicality; and third, the description of the Qur’ân in presenting ideas and psychological situation is very effective and persuasive because it is delivered in the form of a real and coherent picture.